The little pulutan book - Gonzalez, Gene R. (Pinoy classic cuisine series, 2015)
This cookbook offers an assortment of pulutan dishes that are guaranteed to go well with any kind of beer or liquor. There is something here for everyone, form crispy finger foods to fancy meat dishes. For those who love to cook as well as to drink, this little collection of exciting pulutan is sure to please.